2012
DOI: 10.1159/000335342
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in the Rock Hyrax, <i>Procavia capensis</i>

Abstract: We investigated sleep in therock hyrax, Procavia capensis, a social mammal that typically lives in colonies on rocky outcrops throughout most parts of Southern Africa. The sleep of 5 wild-captured, adult rock hyraxes was recorded continuously for 72 h using telemetric relay of signals and allowing unimpeded movement. In addition to waking, slow wave sleep (SWS) and an unambiguous rapid eye movement (REM) state, a sleep state termed somnus innominatus (SI), characterized by low-voltage, high-frequency electroen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 72 publications
(55 reference statements)
1
22
1
Order By: Relevance
“…Given the capacity for the storage and recall of memories by the elephant [33], this potentially intermittent form of REM sleep, where elephants can exhibit no potential REM sleep for up to 9 days (Fig 3), may pose additional problems for functional interpretations of REM sleep related to memory consolidation [34,35]. For the elephant, this would mean that the absolute maximum percent of TST that is occupied by REM sleep would be 12–15%, which appears high compared to its close relatives the manatee (1%) [36] and the rock hyrax (0.4%) [37], but less than that seen in domestic equids which show REM sleep in lateral recumbency (~24%) [31]. In addition, the fact that when recumbent sleep did occur in the wild elephant the episode lengths are similar to those reported in the captive setting (see above), adds additional support to the concept that REM sleep only occurs in recumbency in the elephant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the capacity for the storage and recall of memories by the elephant [33], this potentially intermittent form of REM sleep, where elephants can exhibit no potential REM sleep for up to 9 days (Fig 3), may pose additional problems for functional interpretations of REM sleep related to memory consolidation [34,35]. For the elephant, this would mean that the absolute maximum percent of TST that is occupied by REM sleep would be 12–15%, which appears high compared to its close relatives the manatee (1%) [36] and the rock hyrax (0.4%) [37], but less than that seen in domestic equids which show REM sleep in lateral recumbency (~24%) [31]. In addition, the fact that when recumbent sleep did occur in the wild elephant the episode lengths are similar to those reported in the captive setting (see above), adds additional support to the concept that REM sleep only occurs in recumbency in the elephant.…”
Section: Discussionmentioning
confidence: 99%
“…The fully aquatic Amazonian manatee spends 6.75 h sleeping per day, mostly in slow wave sleep (25% of which is unihemispheric slow wave sleep) and 1% of total sleep time in REM sleep [36]. The rock hyrax, while spending around 7 hours per day asleep, shows not only slow wave and REM sleep (REM being 0.4% of TST), but also a novel sleep state (3% of TST) [37], seemingly associated with variances in the pontine cholinergic system [51]. Thus, the two closest extant relatives of the elephants do show sleep that is not typically mammalian [45], which given the variances in the sleep-associated nuclei noted for the African elephant [16] may indicate that, if polysomnographic recordings of sleep in the elephant were undertaken, novel sleep states, associated with slow wave or REM (REM may form a very small portion of TST in the elephant), may be present in the elephant.…”
Section: Discussionmentioning
confidence: 99%
“…From the 5-second epoch data, the modal state per minute was determined and this per minute modal data was used in all subsequent analyses. The reason we chose to use modal data per minute in our analysis is that in 2 previous studies we have shown that there is no statistically significant difference in the scoring of sleep times and other parameters when using the 1-min modal data [Bhagwandin et al, 2011;Gravett et al, 2012]. Moreover, use of the 5-second epoch data implies that the animals will be having around 600 episodes of slow-wave sleep and wake, of very short duration, every 24 h, which does not make sense in a biological setting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, use of the 5-second epoch data implies that the animals will be having around 600 episodes of slow-wave sleep and wake, of very short duration, every 24 h, which does not make sense in a biological setting. We therefore used the more relevant 1-min modal data for all of our calculations [see Bhagwandin et al, 2011, andGravett et al, 2012, for a detailed analysis of this difference in scoring methods]. The average number and duration of episodes of wake, non-REM sleep and REM sleep were calculated for a 24-hour period, as well as for the light phase and the dark phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation